EscE and EscG Are Cochaperones for the Type III Needle Protein EscF of Enteropathogenic Escherichia coli - Sal-Man, Neta (American Society for Microbiology, 2013)
Type III secretion systems (T3SSs) are central virulence mechanisms used by a variety of Gram-negative bacteria to inject effector proteins into host cells. The needle polymer is an essential part of the T3SS that provides the effector proteins a continuous channel into the host cytoplasm. It has been shown for a few T3SSs that two chaperones stabilize the needle protein within the bacterial cytosol to prevent its premature polymerization. In this study, we characterized the chaperones of the enteropathogenic Escherichia coli (EPEC) needle protein EscF. We found that Orf2 and Orf29, two poorly characterized proteins encoded within the EPEC locus of enterocyte effacement (LEE), function as the needle protein cochaperones. Our finding demonstrated that both Orf2 and Orf29 are essential for type III secretion (T3S). In addition, we found that Orf2 and Orf29 associate with the bacterial membrane and form a complex with EscF. Orf2 and Orf29 were also shown to disrupt the polymerization of EscF in vitro. Prediction of the tertiary structures of Orf2 and Orf29 showed high structural homology to chaperones of other T3SS needle proteins. Overall, our data suggest that Orf2 and Orf29 function as the chaperones of the needle protein, and therefore, they have been renamed EscE and EscG.